Implementation of Differentiated Learning of Sekolah Penggerak Program in Learning in Elementary Schools - Yantoro; Muhammad Sholeh; Anindyta Laila Amalia; Sri Marmoah (Jurnal Penelitian Pendidikan IPA, 2023)
The difference in student’s needs and abilities in learning mathematics made teachers need to vary learning. This study aimed to describe the steps, implementation, and obstacles in the implementation of differentiated learning in mathematics learning in elementary schools. The location of this study was SDN 47/IV Kota Jambi. The subjects of this research were the principal, IVD class teachers, and IVD class students. Qualitative phenomenology was the type of approach used in this study. This study used interview guidelines, observation, and documentation. The data analysis technique used in this study consisted of three stages, namely data reduction, data presentation, and concluding. The results of the study found that differentiated learning in mathematics subjects begins with mapping students' mathematics learning needs, designing learning according to mapping results, and conducting evaluations on an ongoing basis. The implementation of differentiated learning does not mean that in the process it distinguishes all components of learning for one student at a time. The obstacles that are often faced are limited time and lack of experience so it needs adaptation.